The European exposure science strategy 2020–2030. (December 2022) - Fantke, Peter; Bruinen de Bruin, Yuri; Schlüter, Urs; Connolly, Alison; Bessems, Jos; Kephalopoulos, Stylianos; Zare Jeddi, Maryam; van Nieuwenhuyse, An; Dudzina, Tatsiana; Scheepers, Paul T.J.; von Goetz, Natalie
Graphical abstract: Abstract: Exposure science is an emerging and rapidly growing field dedicated to all aspects concerning the contact between chemical, biological, physical or psycho-social stressors and human and ecological receptors. With that, exposure science plays a central role in protecting human and ecosystem health, and contributes to the global transition towards a green and sustainable society. In Europe, however, exposure science is currently not sufficiently recognised as a scientific field, resulting in inefficient uptake into policies. In response, the wider European exposure science community developed elements and actions under the auspices of the Europe Regional Chapter of the International Society of Exposure Science (ISES Europe), for identified priority areas, namely education, exposure models, exposure data, human biomonitoring, and policy uptake. In the present document, we synthesize these strategic elements into an overarching 'European Exposure Science Strategy 2020–2030', following three strategic objectives that focus on acknowledging exposure science as an independent and interconnected field, harmonizing approaches and tools across regulations, and exploring collaboration, education and funding mechanisms. To operationalise this strategy, we present concrete key actions and propose initiatives and funding options for advancing the underlying science, cultivating broader education and cross-sector exposure knowledge transfer, and fostering effective uptake of exposure information into policy. We aim at anchoring European efforts in the global exposure science context, with a special focus on the interface between scientific advancements, application in decision support, and dissemination and training. This will help to develop exposure science as a strong scientific field with the ultimate goal to successfully assess and manage various stressors across sectors and geographic scales.